"A Case-Control Study of Determinative Factors on Malaria Morbidity in Minab, Jask and Roodan Counties, in Hormozgan Province, Southern Iran, 2001" - H Masoumi Asl; M Motabar; Gh Zamani; D Naserinejad; H Vatandoost (Tehran University of Medical Sciences, 2003)
A case control study was performed in three districts in Hormozgan province in 2001 to assess how different determinants affect on malaria morbidity. It assume that results will help the decision makers in all levels of national development program. A total of 384 febrile patients with positive peripheral blood smear were selected as case group, and 753 people with negative peripheral blood smear as control group in three districts ( Minab , Jask , Roodan ) in Hormozgan province during second half of the year 2001. Appropriate questionnaire was designed and data entered twicely. Data were analyzed as matched and unmatched case - control using EPI6 and STATA softwares. Some determinants showed strong and significant relationship with malaria morbidity, including ; illiteracy (OR = 0.59), lack of health house and surrounding as a satellite village (OR = 2.83), far away from health facilities (OR = 1.43), not accessibility to school (OR = 1.75), road (OR = 2.3), screening and curtain (OR = 3.65), electricity accessibility (OR = 1.96), television (OR = 1.50), radio (OR = 1.73), telephone (OR = 2.71), and bed net (OR = 1.69). There was no significant relationship between malaria morbidity and the following determinant: residual spraying in the past 6 months (OR = 1.08). This study indicates that several factors affect on malaria control program. Malaria exists in low socio-economic and undeveloped conditions. Coordination of all sectors and close collaboration among them is a necessary component for malaria control program.